34.1k views
4 votes
Perform the indicated operation x^2-9/x^2 x 2x^3/x^2 + 5x + 6.

User Cvrebert
by
5.6k points

2 Answers

2 votes

Answer:

= x^3+5x^2+6x−18 /x

Explanation:

User Ricka
by
6.0k points
7 votes

Answer:

  • 2x(x - 3)/(x+2)

Explanation:

(x²-9)/x² × 2x³/(x² + 5x + 6)

  • ⇒ a² - b² = (a+b)(a-b)
  • ⇒ x²- 9= (x+3)(x -3)
  • ⇒ x² + 5x + 6 = x² + 2x + 3x + 6= x(x+2) + 3(x+2) = (x+3)(x+2)

Using the above factorization in the given:

  • (x²-9)/x² × 2x³/(x² + 5x + 6)=
  • (x+3)(x-3) × 2x/ (x+3)(x+2) =
  • 2x(x - 3)/(x+2)
User DavidEG
by
6.7k points